The Lady Vanishes: Religious Conflict and Premortem Enshrinement in Sixteenth-Century China - Schneewind, Sarah (The sixteenth century journal, 2021)
This article centers on the career of one sixteenth-century Chinese official, Lin Jun, to connect several religious phenomena of Ming times (1368-1644). The well-known mutual toleration, even syncretism, among Buddhism, Confucianism, Daoism, and the popular religion (referred to by Voltaire) is only one side of Ming religious life. During the high Ming in particular, zealous Confucian officials launched attacks on temples of the other religions, dubbing them "improper shrines." The images of some of these men were placed into shrines to receive offerings while they were alive. Such premortem shrines have been seen as primarily political, but in this case, they honored men who had angered the people of the jurisdiction, and in a sense replaced deities important to the community. Viewing premortem shrines in the light of religious competition suggests that the shrines may have captured a kind of violent spiritual power not normally associated with Confucian officials.